T‐Cell‐Dependent Bispecific IgGs Protect Aged Mice From Lethal SARS‐CoV‐2 Infection - Wenyan Fu; Wei Zhang; Zhongshuai You; Guangyao Li; Chuqi Wang; Changhai Lei; Jian Zhao; Jin Hou; Shi Hu (Advanced Science)
Abstract T‐cell ageing may be a key factor in the disproportionate severity of coronavirus disease 2019 (COVID‐19) in older populations. For hospitalized COVID‐19 patients, treatment involving the use of monoclonal antibodies with the ability to neutralize SARS‐CoV‐2 usually involves the administration of high doses but has not been very effective at preventing complications or fatality, highlighting the need for additional research into anti‐SARS‐CoV‐2 therapies, particularly for older populations. In this study, it is discovered that older persons with a severe SARS‐CoV‐2 infection has weaker T‐cell responses. Therefore the development and characterization of spike‐targeting T‐cell‐dependent bispecific (TDB) full‐length human immunoglobulin Gs with enhanced efficacy in the treatment of COVID‐19 is described. Using S‐targeting TDBs, polyclonal T cells are guided to target and destroy S‐expressing cells, preventing the cell‐to‐cell transmission of SARS‐CoV‐2 and thereby eliminating the need for SARS‐CoV‐2‐specific immunity. Using animal models of COVID‐19, it is shown that the selective activation of T cells improves the efficiency of treatment in preinfected mice by attenuating disease‐induced weight loss and death. The significance of T‐cell‐based immunity during infection is highlighted by the findings. These results have implications for better clinical effectiveness of therapies for COVID‐19 and the development of T‐cell‐dependent medicines for the elderly population.